Sustainable campus design : implementing interactive linkages for a vibrant campus community at Uitm Selangor, Puncak Alam Campus - Abd Nazir, Muhammad Nazreen (2018)
This study is a guide and policy for sustainable campus design at UiTM Selangor, Puncak Alam Campus. It reflects the vision and mission of a vibrant community in the campus to achieve the future sustainability and green campus that refer to the comfortable air, clean water and beautiful landscape. Implementation of the sustainable campus design is aimed at improving the effectiveness of energy consumption, conserving natural resources and improving the quality of the environment. Currently, the physical, social and environmental issues are slightly disturbing a vibrant campus community. Therefore, these problems need to be addressed to ensure the sustainability offered programs of study and development of knowledge among student meet the current demands without prejudice as well as future generation’s opportunity for enjoying the balance of the environment and the wellbeing of the campus. So that, two reference cases such as Taylor’s University Lakeside Campus, Malaysia and University Campus Park in Umea, Sweden be a guide for the author to solve the issues. Through recommended design strategies, design principles, and comprehensive master plan, it is aimed to implement interactive linkages for a vibrant community at UiTM Selangor, Puncak Alam Campus.